Ecogenômica de archaea e monitoramento de comunidades de procariotos redutores de sulfato: aplicações na indústria de petróleo e gás - Carvalho, Ciáxares Magalhães (2008)
The human activities responsible for the ambient degradation in the modern world are diverse. The industrial activities are preponderant in the question of the impact consequences for brazilian ecosystems. Amongst the human activities, the petroliferous industry in operation in Potiguar Petroliferous Basin (PPB) displays the constant risk of ambient impacts in the integrant cities, not only for the human populations and the environment, but also it reaches the native microorganisms of Caatinga ground and in the mangrove sediment. Not hindering, the elaboration of strategies of bioremediation for impacted areas pass through the knowledge of microbiota and its relations with the environment. Moreover, in the microorganism groups associated to oil, are emphasized the sulfate-reducing prokaryotes (SRP) that, in its anaerobic metabolism, these organisms participate of the sulfate reduction, discharging H2S, causing ambient risks and causing the corrosion of surfaces, as pipelines and tanks, resulting in damages for the industry. Some ancestries of PRS integrate the Archaea domain, group of microorganisms whose sequenced genomes present predominance of extremophilic adaptations, including surrounding with oil presence. This work has two correlated objectives: i) the detection and monitoring of the gene dsrB, gift in sulfate-reducing prokaryotes, through DGGE analysis in samples of mDNA of a mangrove sediment and semiarid soil, both in the BPP; ii) to relate genomic characteristics to the ecological aspects of Archaea through in silico studies, standing out the importance to the oil and gas industry. The results of the first work suggest that the petrodegraders communities of SRP persist after the contamination with oil in mangrove sediment and in semiarid soil. Comparing the populations of both sites, it reveals that there are variations in the size and composition during one year of experiments. In the second work, functional and structural factors are the probable cause to the pressure in maintenance of the conservation of the sequences in the multiple copies of the 16S rDNA gene. Is verified also the discrepancy established between total content GC and content GC of the same gene. Such results relating ribosomal genes and the ambient factors are important for metagenomic evaluations using PCR-DGGE. The knowledge of microbiota associated to the oil can contribute for a better destination of resources by the petroliferous industry and the development of bioremediation strategies. Likewise, search to lead to the best agreement of the performance of native microbiota in biogeochemical cycles in Potiguar Petroliferous Basin ecosystem